Summarization of multimedia abstracts using singular value decomposition on histograms (SMASH) - Del Castillo, Juancho I.; Santos, Vergel Lucino P.; Tan, Stephanie Joyce P. (2004)
A video abstract is an optimal and concise summary of a longer video document which contains a sequence of associated dynamic images. Video abstraction aims to transform an entire video into a small number of representative frames while preserving the essential content of the original document. It suggests extracting significant segments of a video document containing the core of the original object without disruptions in the presentation medium. In this age of advanced technology and wide multimedia usage, the biggest challenge researchers are faced with is to develop a successful automated video abstraction system that will generate a summary of a video document with minimal screening time. Security is very essential, nowadays, in every aspect of protecting the corporate world. With the current technological innovation, most establishments resort to video surveillance as their primary means of internal security. Applying video abstraction to surveillance videos is really challenging since this kind of videos are voluminous, unstructured, and, are most of the time, focused on a single spot - capturing all the events on that particular location, thus creating a static environment for the video. With this, the process of video abstraction becomes more complex and difficult. In line with this challenge, there is an urgent need to make available a system that can aid in the processing of surveillance videos along with the assurance that the output retains the significant fractions of the surveillance. There are several approaches already presented in completing the challenges mentioned above. In this paper, a scheme for video abstraction using Singular Value Decomposition (SVD) is presented. SVD is performed on a feature-frame matrix whose values are computed from color histograms in the RGB (Red-Green-Blue) color space. Using the resulting values, the feature space dimensions are reduced to enhance the clustering of visually similar images. The degree of visual changes in a video sequence is a good indicator of the amount of visual content contained in each video. With Singular Value Decomposition, the video abstract contains little redundancy, thus preserving the basic content of the original video. SMASH is an automated, real-time summarization system that enables direct and continuous processing between the computer and the attached camera. In extracting the video streams from the camera, the frame rate and size of the input can be adjusted. The system automatically runs through the captured files and produce their respective summaries. Furthermore, the system can summarize any video that is of Quicktime movie format (i.e. .mov files).
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Automatic abstracting; Digital video; Streaming video